Green Economy as a Sustainability Strategy for Cikole Bandung Civet Coffee Production: Green Economy sebagai Strategi Keberlanjutan Produksi Kopi Luwak Cikole Bandung - Tasya Novia Sari; Shinta Eka Meilinda; Ananda Keisha Maulid Nabila; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The specialty coffee sector increasingly faces scrutiny regarding environmental impacts and ethical production standards. Specific Background Civet coffee production requires balancing economic profitability, ecological preservation, and animal welfare compliance. Knowledge Gap Comprehensive field frameworks integrating natural geographical advantages, traditional processing, and byproduct upcycling within civet coffee operations remain inadequately documented. Aims This study analyzes the implementation of green economy principles at Cikole Luwak Coffee as a sustainable production model. Results The operation successfully leverages Lembang highland geography for natural temperature regulation, natural enzymatic digestive fermentation, solar drying energy efficiency, eco-education tourism, and coffee waste upcycling into cosmetic products. Novelty This research establishes an empirical five-dimension green economy framework combining animal welfare compliance with circular bioeconomy practice in specialty coffee agritourism. Implications Practitioners can adopt these integrated ecological operations to mitigate international welfare criticisms while enhancing product value and tourism revenue. Key Findings Highlights Natural highland geographic conditions and solar drying methods eliminate the need for energy-intensive processing technologies. Integrating animal welfare standards with eco-education tourism creates sustainable revenue streams beyond raw coffee sales. Upcycling coffee production residues into skin cosmetic products achieves zero-waste operational goals. Keywords: Green Economy, Civet Coffee, Production Sustainability, Agrotourism, Circular Economy